A simplified damage prediction framework for milling of unidirectional carbon fiber-reinforced plastics. (2nd October 2015) - Islam, F.; Ramkumar, J.; Milani, A.S.
Abstract: This article presents a simple framework for predicting the occurrence of delamination during milling of unidirectional carbon-fiber-reinforced plastics (CFRPs), based on a concept of effective critical cutting zone . To validate the concept, sets of milling experiments were conducted on unidirectional CFRP samples of varying fiber orientations and the delamination signature was measured through microscopic images. By observing the damage extent for different fiber orientation angles and different fiber cutting angles for up-milled and down-milled edges, and correlating them with different material removal mechanisms, it has been shown that the damage mainly depends on the portion of the fiber cutting angles that lie within the effective critical milling zone. Both the delamination and the normal cutting forces were found to be strongly dependent on the range of angles in this zone. In addition, it is shown that the cutting force may be used as a good approximation to determine the effect of machining/process parameters on the ensuing delamination damage during milling of CFRPs. For the tested samples, the normal cutting force decreased with an increase in the cutting speed and it increased with an increase in the feed rate of the cutting tool. Abstract :